Endoscopic Surgery of Nasopharyngeal Angiofibroma - Zimmermann, Elise; Selonke, Ian; Gavazzoni, Fabiano Bleggi; Pereira, Rodrigo Guimarães; Machado, Silvio; Tanamati, Tatiane Kimmi (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Juvenile nasopharyngeal angiofibroma (NAJ) is a tumor with vascular component, slow growing, benign but very aggressive because of its local invasiveness. The NAJ is rare, accounting for 0.05% of all head and neck cancers. The classic triad of epistaxis, unilateral nasal obstruction and a mass in the nasopharynx suggests the diagnosis of NAJ and is then supplemented by imaging. Over the past 10 years the treatment of this disease has been discussed with the aim of designing a management protocol. Currently, surgery appears to be the best treatment of the NAJ. Other methods such as hormone therapy, radiotherapy and chemotherapy treatment modalities are now used occasionally as complementary treatments.Objective: To present the cases of this disease in the Hospital Infantil between October 2007 and August 2008.Methods: A retrospective case study of five cases of NAJ underwent surgery solely with endoscopic technique of two surgeons. Classifieds between IIA and IIIA. All patients underwent angiography with embolization of the tumor 3-4 days before surgery. Follow-up after surgery to detect recurrence.Results: There were two relapses in the following two years after surgery.Conclusion: Given the short period of patient follow-up, there were only two relapses in one year. So there is need for further action to claim that this technique has a low recurrence rate, since the recurrence is probably related to incomplete resection the initial tumor.
Keywords: angiofibroma; therapy; endoscopy; recurrence